The age of scientific naturalism : Tyndall and his contemporaries - Lightman, Bernard V., 1950-; Reidy, Michael S. (Science and culture in the nineteenth century, 2016)
Physicist John Tyndall and his contemporaries were at the forefront of developing the cosmology of scientific naturalism during the Victorian period. They rejected all but physical laws as having any impact on the operations of human life and the universe. Contributors focus on the way Tyndall and his correspondents developed their ideas through letters, periodicals and scientific journals and challenge previously held assumptions about who gained authority, and how they attained and defended their position within the scientific community.